Publications of James Edward Oglethorpe - Arnold, Eli (Georgia Open History Library, 1994)
Publications of James Edward Oglethorpe contains various writings by the founder of the Georgia colony, supplemented by introductions and notes to further the reader's understanding of the texts. The collection of articles, letters, essays, and reports gives a reader insight into the life and mind of the man who shaped the history of the state of Georgia with an agenda of social reformation. This book satisfies a reader's curiosity both regarding Oglethorpe himself as well as life in the colony, through its inclusion of colony reports alongside letters in which Oglethorpe expands on his ideas about British America. The Georgia Open History Library has been made possible in part by a major grant from the National Endowment for the Humanities: Democracy demands wisdom. Any views, findings, conclusions, or recommendations expressed in this collection, do not necessarily represent those of the National Endowment for the Humanities.